PEMANFAATAN GEOBOARD DAN KARET GELANG UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA BANGUN DATAR - Istikomah, Istikomah (Universitas Insan Budi Utomo, 2020)
Lack of student interest in learning mathematics is a scourge that needs immediate action. In this study, researchers used the media geoboard and rubber bands as a tool to increase interest in learning. The study was conducted with Classroom Action Research which was successfully completed in two cycles. The results of this study are increased student interest in mathematics before taking action only 12 students, after cycles I and II, made 20 students interested in a total of 22 students. Increasing learning outcomes and concept understanding was very good. At the end of the action in the second cycle it was found that all students had understood the concept of calculating area and circumference of rectangular and triangular shapes.